The girl who tested the waters : Ellen Swallow, environmental scientist - Daniele, Patricia (MIT Kids Press, 2025)
Ellen Swallow found a friend in nature and a lifelong love of science as a child exploring the woods around her family's home. She was a voracious learner with an interest in chemistry, and continuing her education at the newly established Massachusetts Institute of Technology seemed a good fit. But in 1871, many believed that women belonged in the home, not in schools dedicated to the study of science. Ellen thought, why not both? She believed science could help solve the problems of everyday life, including the pollution she observed in Boston, so when offered the chance to study the city's water systems, she seized it. What she found would change the way we think about clean water. In her lifetime, Ellen pioneered science education for women, advocated for a healthier environment, and helped develop the field of ecology. The Girl Who Tested the Waters, with engaging text and soft, inviting illustrations, portrays a woman ahead of her time and her tireless efforts to bring about change for good. Curious readers can find more in the back matter, including a time line, an author's note, source notes, and a bibliography.